Perancangan Interior Nestlé’s Cereal World di Surabaya - Linda Gunawan; mariana wibowo (Intra, 2014)
Nestlé’s Cereal World is a new facility in foodservice industry, which people can explore and obtain a new experience about cereal through 4 main facilities: attraction, discover, dining, and shopping. Nestlé’s Cereal World design will use Nestlé’s interior branding, which the tangible and intangible design will represent the Nestlé’s Cereal identity.